KONTRIBUSI KECERDASAN EMOSIONAL DAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU - Bernawati, Yenni; M Amin, Maswardi; Radiana, Usman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine how high the contribution of emotional intelligence and managerial ability of school principals to the performance of teachers in the SMA Negeri Keramat Bay, partially and jointly.. This research uses descriptive quantitative correlational. In this study the population is all high schools in the District of Teluk Keramat District. This research was conducted in 4 schools with 82 teachers. Where there were 38 male teachers and 44 female students. Determination of the sample using the Proportional Random Sampling Technique with an error rate of 5%, and the number of samples there are 68 people. The instrument used was a questionnaire or questionnaire. The collected data were analyzed using multiple linear regression analysis through the IBM SPSS 25 (SPSS 25) program. The conclusions of this research are as follows: (1) The principal's emotional intelligence in the upper middle school of the sacred gulf sprouts is low. (2) The principal's managerial skills at the upper middle school of the sacred gulf denunciation are still low. (3) The performance of teachers in high school of the sacred gulf sprouts was high. (4) There is a significant contribution between the principal's emotional intelligences to the performance of teachers in high school countries of the sacred gulf denunciation.(5) There is a significant contribution between the principal's managerial skills to the performance of a country's high school teacher the sacred gulf sprouts. (6) There is a significant contribution of the principal's emotional intelligence and the principal's managerial ability jointly to the teacher's performance at the state high school sacred gulf denunciation.Key Word : Emotional Intelligence, Managerial Ability, Teacher Performance